Proton MR Spectroscopy and MRI-Volumetry in Mild Traumatic Brain Injury - Cohen, B.A.; Inglese, M.; Rusinek, H.; Babb, J.S.; Grossman, R.I.; Gonen, O. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: More than 85% of brain traumas are classified as “mild”; MR imaging findings are minimal if any and do not correspond to clinical symptoms. Our goal, therefore, was to quantify the global decline of the neuronal marker N-acetylaspartate (NAA), as well as gray (GM) and white matter (WM) atrophy after mild traumatic brain injury (mTBI).MATERIALS AND METHODS: Twenty patients (11 male, 9 female; age range, 19−57 years; median, 35 years) with mTBI (Glasgow Coma Scale score 13−15 with loss of consciousness for at least 30 seconds) and 19 age- and sex-matched control subjects were studied. Seven patients were studied within 9 days of TBI; the other 13 ranged from 1.2 months to 31.5 years (average and median of 4.6 and 1.7 years, respectively) after injury. Whole-brain NAA (WBNAA) concentration was obtained in all subjects with nonlocalizing proton MR spectroscopy. Brain volume and GM and WM fractions were segmented from T1-weighted MR imaging and normalized to the total intracranial volume, suitable for intersubject comparisons. The data were analyzed with least squares regression.RESULTS: Patients with mTBI exhibited, on average, a 12% WBNAA deficit that increased with age, compared with the control subjects (p < .05). Adjusted for age effects, patients also suffered both global atrophy (−1.09%/year; P = .029) and GM atrophy (−0.89%/year; P = .042). Patients with and without visible MR imaging pathology, typically punctate foci of suspected shearing injury, were indistinguishable in both atrophy and WBNAA.CONCLUSION: WBNAA detected neuronal/axonal injury beyond the minimal focal MR-visible lesions in mTBI. Combined with GM atrophy, the findings may provide further, noninvasive insight into the nature and progression of mTBI.